2020
DOI: 10.1590/1678-7757-2019-0771
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide nanotubes incorporated into bleaching agents: physicochemical characterization and enamel color change

Abstract: Titanium dioxide nanotubes incorporated into bleaching agents: physicochemical characterization and enamel color change Titanium dioxide nanotubes are nanostructures that can accelerate the oxidation reaction of bleaching procedures and promote a more effective whitening effect. Objective: This study evaluated physicochemical properties of bleaching agents incorporated with titanium dioxide (TiO 2) nanotubes, and the effects on tooth color change at different periods. Methodology: 40 premolars were treated acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
1
7
0
1
Order By: Relevance
“…43 It has the property of depositing a thin layer of pigment on the tooth surface, shifting the color of the substrate toward blue, due to changes in the interaction with the incident light, and consequently, the substrate appears lighter. Even so, the effect of this chemical component on tooth color change deserves further investigation, 44 especially because in the present study, the toothpastes were not able to promote tooth whitening.…”
Section: Discussionmentioning
confidence: 73%
“…43 It has the property of depositing a thin layer of pigment on the tooth surface, shifting the color of the substrate toward blue, due to changes in the interaction with the incident light, and consequently, the substrate appears lighter. Even so, the effect of this chemical component on tooth color change deserves further investigation, 44 especially because in the present study, the toothpastes were not able to promote tooth whitening.…”
Section: Discussionmentioning
confidence: 73%
“…There are multiple applications of commercially available titanium nanoparticles in medicine and dentistry [ 9 ], such as cell imaging, biosensors of biological assays, drug delivery systems, photodynamic therapy for cancer and genetic engineering in medicine [ 10 ]. The vast utilization of titanium nanoparticles in clinical dentistry includes composite adhesives and bonding agents [ 11 ], glass ionomer cement restorations [ 11 , 12 , 13 ], dental implants [ 14 ], bleaching and whitening agents [ 15 ], irrrigants in root canal treatment, mouth washes, tooth pastes and polishing pastes [ 16 ]. Previously, titanium nanoparticles enhanced the antimicrobial properties and bond strength of composites in orthodontics [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings contradict the results published by Pretel et al [ 43 ], because, even though commercial gels modified by the incorporation of N_TiO 2 (produced by calcination strategies) displayed initial pH values that were high, the materials investigated [ 43 ] displayed pH values that were significantly lower after 30 min of observation. On the other hand, Monteiro et al [ 44 ] have shown that the incorporation of 1% TiO 2 nanotubes did not adversely impact the pH values of gels containing either 10% carbamide peroxide (pH ≅ 6.5) or 40% HP (pH ≅ 7.0). These differences in pH values reported in the literature and by the present study (initial and after 30 min) can be explained by the intrinsic differences in materials’ compositions including the type of polymeric matrix and stabilizing agents.…”
Section: Discussionmentioning
confidence: 99%